WORK FROM HOME: EFFECTS ON THE HEALTH AND PRODUCTIVITY OF FEMALE EMPLOYEES - Vandana Singh; Kapil Bansal (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
Work from home has a potential to provide notable changes to both employees and employers but have substantial challenges too. This paper contains work from home among information technology (IT) sector employees categorically exploring distinction between time use of home-based men and women workers and how telecommuting influences the health and productivity of women in the workplace. The data was collected by survey. The research uses a sample of 370 participants. We used SPSS to analyses the data. The data indicate that working remotely has a substantial effect on the health of female employees